HISTORIS DAN TRADISI ZIARAH MAKAM BUYUT SAYU ATIKAH DI BANYUWANGI - Mahfud, Mahfud; Yudiana, I Kadek; Fatimah, Siti (Nusantara Hasana Journal, 2022)
Tomb pilgrimage is a form of culture or customs for some people in Indonesia. And tomb pilgrimages, carried out by visiting the graves of guardians, scholars, and also family graves. And in this study aims to study or analyze related to the history and tradition of the pilgrimage to the Tomb of the Great-grandfather Sayu Atikah. This study uses a qualitative descriptive method of phenomena that occur in habits that have been passed down from the community's ancestors by making a pilgrimage to the Tomb of Sayu Atikah's great-grandfather. The method of data collection in this study used the method of observation and interviews with several respondents who became the data source. Results and discussion in this study. First, related to the history of the tomb historically, it can also be concluded that the existence of the tomb of Buyut Atika is historical evidence of the spread of Islam in the land of Blambangan, which has existed since the 14th century, since the birth of Sunan Giri, who was born to Sheikh Maulana Ishaq and Dewi Sekardadu or Sayu. Atika. Sayu Atika's tomb is believed to be the oldest Islamic tomb in Banyuwangi. The tradition of pilgrimage to the tomb at Buyut Sayu Atikah is a form of tradition or customs handed down by ancestors. Pilgrimage is an activity carried out to ask for prayer or to pray for people who have died. The pilgrims who visit the tomb of Buyut Sayu Atikah, are based on intentions, goals that are driven by a solid goal, both fulfilling vows, asking for a better life and various other requests.